Analisis Pemahaman Mahasiswa Akuntansi terhadap Konsep Dasar Akuntansi - Reny Wardiningsih (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2020)
This study aims to examine the understanding of Accounting Students related to the basic concept of accounting, namely the understanding of assets, liabilities and capital based on the background of secondary schools (Vocational Accounting, Social Sciences and Natural Sciences Senior High School). Sampling through a purposive sampling technique that is a number of 90 accounting students from Mataram University and Mataram University of Technology who filled out the research questionnaire. This study uses SPSS 18 data processing, with a different test, testing the hypothesis shows the result that H3 is accepted, which is a significance level of 0.044 where the value is less than 0.05; and concluded that there are significant differences regarding the understanding of capital between students from SMK Accounting, SMA IPS and IPA SMA, while H1 and H2 are not accepted, the significance level is 0.724 and 0.874, respectively, where the value is greater than 0.05. This happens due to several factors including: lack of practice, lack of practice, short study portions, etc., causing a lack of understanding of students towards assets and liabilities which are important indicators of other financial statements.